Community land formalization and company land acquisition procedures: A review of 33 procedures in 15 countries. (November 2021) - Notess, Laura; Veit, Peter; Monterroso, Iliana; Andiko; Sulle, Emmanuel; Larson, Anne M.; Gindroz, Anne-Sophie; Quaedvlieg, Julia; Williams, Andrew
Highlights: Community land, crucial to rural livelihood, is increasingly targeted by commercial interests, leading to degradation, poverty, and disputes. Without formal legal recognition of their land rights, communities often struggle to protect their land from being allocated to investors. Procedures to register and document customary land rights are often complex, difficult, costly, and can take decades to complete. Companies acquire formal land rights relatively quickly with some taking shortcuts or beginning operations before obtaining final approvals. Few laws require foreign companies to engage in meaningful community consultation, disadvantaging responsible companies. Communities benefit from clear, accessible procedures and conflict resolution mechanisms, and strong oversight of company behavior. Abstract: Indigenous and community lands, crucial for rural livelihoods, are typically held under informal customary tenure arrangements. This can leave the land vulnerable to outside commercial interests, so communities may seek to formalize their land rights in a government registry and obtain an official land document. But this process can be time-consuming and complex, and in contrast, companies can acquire land relatively quickly and find shortcuts around regulatory burdens. This article reviews and maps 19 community land formalization and 14 company land acquisition procedures is 15 countries in Africa, Asia and Latin America. Comparing community and company procedures identifies multiple sources of inequity.